2019
DOI: 10.24293/ijcpml.v25i1.1485
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Free Hemoglobin Level and Plasma Nitric Oxide in Packed Red Cell During Blood Bank Storage Period

Abstract: Stored red blood cells undergo morphological and biochemical changes with increased storage time, commonly refferred as the storage lesion, reduced integrity of erythrocyte membrane, causing hemolysis and increased free plasma hemoglobin level. Nitric Oxide (NO) is an endogenous vasodilator with the major role in vascular and blood flow regulation. Accumulation of free hemoglobin (fHb) during storage RBC hemolysis is thought to be correlated with elevated NO consuming causes low NO level that significantly imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Fitria's study showed a significant increase in haemoglobin for 28 days. first, the seventh day, fourteenth day, twenty-first day, and twentyeighth day [11]. In other cases hemolysis were found of the red cells increases due to processing and during storage and is maximum during the first week.…”
Section: Haemoglobinmentioning
confidence: 94%
“…Fitria's study showed a significant increase in haemoglobin for 28 days. first, the seventh day, fourteenth day, twenty-first day, and twentyeighth day [11]. In other cases hemolysis were found of the red cells increases due to processing and during storage and is maximum during the first week.…”
Section: Haemoglobinmentioning
confidence: 94%
“…2 Penelitian tahun 2019 oleh Fitria et al menunjukkan hasil peningkatan kadar hemoglobin pada PRC yang disimpan selama 28 hari, yaitu 0,03 g/dL pada hari penyimpanan ke-0 dan 0,26 g/dL pada hari penyimpanan ke-28. 3 Penyimpanan PRC dapat mempengaruhi nilai hematokrit. Hematokrit atau volume sel darah merah terkompresi dalam darah yang disimpan dapat meningkat karena perubahan morfologi eritrosit selama penyimpanan.…”
Section: Abstrakunclassified